Old Testament Mythology in its Ancient Near Eastern Context - Lambert, Wilfred G.
Appendix I: The Reading of the Theophorous Element NI (=Ya?) in Eblaite Personal Names. Appendix II: Readings of the Name of the Ugaritic God kṯr.